The Impact of Women’s Electronic Lifestyle on Advertising Acceptance and Intention to Purchase Online: A Structural Analysis - Sara Mohammadi; Eslam Fakher; Ali Mehrabi; Khadijeh Safikhani Nasimzadeh (زن در توسعه و سیاست)
The electronic lifestyle is now closely linked to the advancement of the Internet. It is imperative to comprehend the lifestyle and style of individuals in order to deliver the most suitable services to their respective departments. Therefore, it seems that according to the technological developments and the use of new technologies, people's electronic lifestyle is a tool for marketing and designing services based on information and communication technology. The purpose of this study is to investigate the impact of an electronic lifestyle on the acceptability of advertisements and the intention to purchase online among women in Ahvaz City. Consequently, this investigation is classified as an applied research in terms of its nature and objective, and it is a descriptive-correlational research in terms of its data collection methodology. The statistical population consists of all female citizens of Ahvaz who have experience with online purchasing. A sample of 384 individuals was selected through non-random sampling. Structural equation modeling and SmartPLS software were employed to analyze the validity and reliability of data collected using conventional questionnaires. The data analysis results indicated that the intention to purchase online is significantly influenced by the categories of electronic lifestyles, with the exception of the sociable and emergency-oriented lifestyles. Additionally, advertisements’ acceptance and the intention to purchase online were both substantially confirmed by the impact of electronic lifestyles. Nevertheless, the mediating function of advertising acceptance in the effect of e-lifestyle on intention to shop online was positive but non-significant, and it was not confirmed.